16‐QAM OFDM‐Based K‐Band LoS MIMO Communication System with Alignment Mismatch Compensation. Issue 4 (August 2017) - Kim, Bong‐Su; Kim, Kwang‐Seon; Kang, Min‐Soo; Byun, Woo‐Jin; Song, Myung‐Sun; Park, Hyung Chul
Abstract : This paper presents a novel K‐band (18 GHz) 16‐quadrature amplitude modulation (16‐QAM) orthogonal frequency‐division multiplexing (OFDM)‐based 2 × 2 line‐of‐sight multi‐input multi‐output communication system. The system can deliver 356 Mbps on a 56 MHz channel. Alignment mismatches, such as amplitude and/or phase mismatches, between the transmitter and receiver antennas were examined through hardware experiments. Hardware experimental results revealed that amplitude mismatch is related to antenna size, antenna beam width, and link distance. The proposed system employs an alignment mismatch compensation method. The open‐loop architecture of the proposed compensation method is simple and enables facile construction of communication systems. In a digital modem, 16‐QAM OFDM with a 512‐point fast Fourier transform and (255, 239) Reed‐Solomon forward error correction codecs is used. Experimental results show that a bit error rate of 10 −5 is achieved at a signal‐to‐noise ratio of approximately 18.0 dB.